Adhesion of fourteen milimeters chip seal at different aggregate and binder rates [electronic resource] - Nurhaziyah Mahdan, 1988-, author (2011)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2011